RISK ANALYSIS OF DIGITAL LOAN COMPARISON PLATFORM - Ščetilnikova, Jelena; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
Advanced technologies can improve the efficiency of business processes, but incorrect system implementation can also become a huge source of damage. Therefore, the issue of IT security is very important. The concept of IT security has many aspects. One of them is security risk analysis, which must be considered by each system developer. The article describes one of the risk analysis methods - the CORAS method. The goal of research was to complete the risk analysis of the loan comparison platform. As a result, the risk mitigation recommendations were developed.